The Dose Response of Taurine on Aerobic and Strength Exercises: A Systematic Review - Chen, Qi; Li, Zheng; Pinho, Ricardo A.; Gupta, Ramesh C.; Ugbolue, Ukadike C.; Thirupathi, Anand; Gu, Yaodong (Frontiers in Physiology, 2021)
Taurine is a naturally occurring amino acid and is involved in various roles such as regulating ion channels and cell volume and stabilization of membranes. However, how this molecule orchestrates such functions is unknown, particularly dose response to exercised muscles. Therefore, this review was aimed to systematically review the dose response of taurine during both aerobic and strength exercises on muscular performance. According to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, a search for relevant articles was carried out on PubMed/Medline, Web of Science, and Google Scholar using related terms such as taurine, exercise performance, exercise, muscle, physical training, running, strength, endurance exercise, resistance exercise, aerobic exercise, and swimming. The following parameters were used to assess the exercise performance in the selected studies: creatine kinase (CK), lactic acid dehydrogenase, carbohydrate, fat, glycerol, malondialdehyde, enzymatic antioxidants, blood pH, taurine level, and muscular strength. From the selected literature, we observed that taurine supplementation (2g/3 times a day) during exercise can decrease DNA damage or taurine supplementation (5g/day) before or after the exercise can decrease the lactate level. However, higher dose of taurine (6g) before the exercise had no effect on reducing lactate level, but it increased the glycerol level, suggesting taurine could be an effective agent for prolonged activities especially with higher intensities. However, further studies are warranted to establish the role of taurine on fat metabolism during exercise. Next, we observed that low dose of taurine (0.05g) before performing strength exercise can decrease the muscular fatigue and increase enzymatic antioxidants, but additional studies are required to prove whether taurine supplementation could be a useful candidate before or during and after the strength exercise. Systematic review registration number PROSPERO (Registration number is: CRD42021225243) http://www.crd.york.ac.uk/PROSPERO.